Electron microscopy of the intestine of gnotobiotic piglets infected with porcine rotavirus - Narita, M. (J Comp Pathol, 1982)
Five gnotobiotic piglets inoculated orally with porcine rotavirus developed an enteric lesion. Electron microscopy of the mucosal epithelium 12 h after inoculation showed that the virus penetrates into the absorptive cells between microvilli, possibly by a pinocytic mechanism. Afterwards, virus particles were most often seen within dilated cisternae of the rough endoplasmic reticulum (RER). These infected cells showed a range of changes, such as disruption of the microvilli, loss of cytoplasmic density and deposition of lipid droplets. Subsequently, most of the epithelial cells were desquamated from the villi. The interaction of virus and intestinal cells thus indicates that rotavirus is pathogenic for the epithelial cells.